Distribution of the leaf-eater (Galerucella luteola Müll) in Khorezm region - Ruzmetova Muxabbat Xujaniyazovna; Jumaniyozova Gulyor Yodgor qizi (Zien Journals, 2023)
this article describes the biology, larvae, mushroom, egg, adult beetle (Galerucella luteola Müll) and its development during the season, necessary conditions for their development.
Keywords: egg; larva; sponge